Partially Implicit FDTD (PI-FDTD) Method for Lower Dispersion and Anisotropic Errors - Mehmet Kusaf; Abdullah Yucel Oztoprak (IEEE Access, 2022)
A new partially implicit 3D FDTD (PI-FDTD) method is introduced. The method is not unconditionally stable, but its stability limit is 6 times higher than that of the classic Yee’s FDTD method. The method has only one implicit update equation and uses four split time steps. A study has been carried out to compare the performances of the new method and the ADI-FDTD, LOD-FDTD, and HIE-FDTD methods. ADI-FDTD and LOD-FDTD methods are unconditionally stable and the HIE-FDTD method is conditionally stable with a stability limit of 3.46 times above the Yee’s FDTD method. The dispersion and anisotropic errors of the PI-FDTD method are considerably lower than that of these methods and for small cell sizes, the new method is almost isotropic. For example at the stability limit of the PI-FDTD method with a uniform cell size of $λ \mathord {\left /{ {{ {50}}} }\right. }$ the maximum dispersion errors and anisotropic errors are 0.15% and 0.031% for the new method and 1.66% and 0.64% for the ADI-FDTD and LOD-FDTD methods. At the stability limit of the HIE-FDTD method, the maximum dispersion errors and anisotropic errors of the PI-FDTD method are also less than HIE-FDTD, ADI-FDTD, and LOD-FDTD methods. The differences in errors are more pronounced for larger cell sizes. Although the new method uses a four time split step scheme and the ADI-FDTD and LOD-FDTD methods use a two time split step scheme, the computational time of the PI-FDTD method is less, as it uses an implicit scheme for only one of the field components when updating. The computational time of the PI-FDTD method is the same as that of the HIE-FDTD method. The study has revealed that the new method can be used over much wider frequency bandwidths.